CHANGES IN NITRIC OXIDE PRODUCTION AND DEVELOPMENT OF OXIDATIVE STRESS IN RATS HEART DURING PROLONGED TRIPTORELIN-INDUCED CENTRAL DEPRIVATION OF LUTEINIZING HORMONE SYNTHESIS - Voroshilova, T.A.; Shepitko, V.I.; Stetsuk, Ye.V.; Akimov, O.Ye.; Puzyryov, G.S. (World of Medicine and Biology, 2022)
Disruption of synthesis of luteinizing hormone may lead to testosterone deficiency. And testosterone deficiency leads to increased risk of cardiovascular mortality and aggravates coronary artery disease. On the 180th day we observed the biggest shift towards M1 phenotype. This event coincided with the increased SAR production. Since M1 polarized tissue macrophages have the ability to produce reactive oxygen and nitrogen species we can speculate that highest lipid peroxidation observed in our study on the 180th day of the experiment is connected with changes in macrophage polarization towards predominance of M1 phenotype. Therefore, we can conclude, that decrease in oxidative damage to the heart on the 30th day of the experiment can be connected to lower concentration of luteinizing hormone. On later terms of the experiment activation of xanthine oxidase/uric acid signaling due to the lack of testosterone causes the development of oxidative stress. Decrease in activity of antioxidant enzymes during peak production of SAR (180th day) can be explained by exhaustion of these enzymatic systems.
Keywords: nitric oxide; oxidative stress; heart; rats; luteinizing hormone; triptorelin